Double Brillouin frequency shift through circulation of odd-order Stokes signal - Shee Y.G.; Al-Mansoori M.H.; Ismail A.; Hitam S.; Mahdi M.A. (OSA - The Optical Society, 2023)
We demonstrate a simple configuration for generating a double Brillouin frequency shift through the circulation of an odd-order Brillouin Stokes signal. It is operated based on cascaded Brillouin scattering in single-mode optical fibers that behave as the Brillouin gain media. A four-port circulator is incorporated into the setup to circulate the odd-order Brillouin Stokes signal in the fiber. It thus initiates a higher order Brillouin Stokes signal, which is double Brillouin frequency downshifted from the input signal. For the 5km long fiber, the Brillouin pump power at 23mW gives a clean output spectrum with 30 dB sideband suppression ratio. The output signal is 0.174nm or ?21.7GHz downshifted from the input signal. 2010 Optical Society of America.